2022
DOI: 10.1186/s13756-022-01107-w
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey on the implementation of infection prevention and control components in 1442 hospitals in the Republic of Korea: comparison to the WHO Infection Prevention and Control Assessment Framework (IPCAF)

Abstract: Background The current SARS-CoV-2 pandemic continues to underscore the inadequacy of infection prevention and control (IPC) and the importance of its sound establishment in healthcare facilities. The Infection Prevention and Control Assessment Framework (IPCAF) by the World Health Organization allows systematic assessment of IPC capacity in healthcare facilities and has been applied in many national-level surveys. This study aims to assess the IPC capacity of Korean hospitals as well as their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
0
17
2
Order By: Relevance
“…Developed countries have implemented key aspects of the IPC program and have achieved good levels of implementation through mostly advanced practices [23,24]. These results can be explained by the contribution of existing legislation the strong involvement of policy makers, the implementation of IPC budget [19]. Indeed, in 2011, the German Infection Protection Act ("Infektionsschutzgesetz") was revised, increasing the importance of IPC in hospitals [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed countries have implemented key aspects of the IPC program and have achieved good levels of implementation through mostly advanced practices [23,24]. These results can be explained by the contribution of existing legislation the strong involvement of policy makers, the implementation of IPC budget [19]. Indeed, in 2011, the German Infection Protection Act ("Infektionsschutzgesetz") was revised, increasing the importance of IPC in hospitals [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have proven the feasibility and effectiveness of these guidelines using the evaluation frameworks proposed by the WHO in several countries around the world [15][16][17][18], much remains to be done, especially in developing countries [9,11,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Developed countries have implemented key aspects of the IPC program and have achieved good levels of implementation through mostly advanced practices [23,24]. These results can be explained by the contribution of existing legislation, the strong involvement of policy makers, and the implementation of the IPC budget [19]. Indeed, in 2011, the German Infection Protection Act ("Infektionsschutzgesetz") was revised, increasing the importance of IPC in hospitals [17].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment tool was based on a modi ed version of the IPC Assessment Framework (IPCAF) on Core Components of IPC and the recommendations included in the WHO "Guidelines on Core Components of Infection Prevention and Control Programs at the National and Acute Health Care Facility Level" (WHO, 2018). The IPCAF is primarily intended to be used by facilities as a self-assessment tool but can also be successfully used for the purpose of joint external assessments (Deryabina et al, 2021;Jeong et al, 2022). A study published in 2020 highlights that effective utilization of the IPCAF tool requires a deep understanding of the WHO terminology and underlying concepts to avoid misinterpretation and misreporting of data (Tomczyk et al, 2020).…”
Section: Pilot Study and Data Collectionmentioning
confidence: 99%
“…Our results show that guidelines and SOPs on prevention of MDR pathogens were available only at 10% of hospitals. Limited availability of guidelines on antibiotic stewardship and prevention of MDR pathogens was also noted in facility-level studies conducted in other countries, such as Georgia and Korea(Deryabina et al, 2021;Jeong et al, 2022).Although 45% of hospitals reported conducting routine HCAI surveillance, only one hospital had an HAI surveillance system that included all of the key WHO recommendations. A global survey of national-level IPC core components published in 2021 showed that less than half of the 88 countries surveyed had established national surveillance networks on HAIs(Tartari et al, 2021).…”
mentioning
confidence: 99%